The Neo-Schumpeterian Growth Model with the Capital Market - Burzyński , Michał; Malaga , Krzysztof (Studia Oeconomica Posnaniensia, 2026)
The purpose of this article is to answer the four questions: what is the dynamic equilibrium between the nominal sphere (capital market) and the real sphere (production, innovation, technological progress) of the economy? How do the maturity and liquidity of the capital market influence long-term growth? What is the impact of the relative risk aversion of investors on the process of innovation? How does long-term volatility in the capital market influences economic growth? To answer these questions we have built the model of growth of the the capital market. It extends the Aghion and Howitt model [2009], which belongs to the group of neo-Schumpeterian models. It is an endogenous growth model in which the rate of growth depends on technological progress that results from innovations implemented in the economy in a random manner. Based on that model, after calibration of its parameters, we have presented the results of the application of the Monte Carlo method to the simulation of an economy's dynamics on both microeconomic and macroeconomic levels.